2021
DOI: 10.3390/polym13081295
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of New Sol–Gel Hybrid Inulin–TEOS Adsorbent

Abstract: A new biopolymer–silica hybrid material consisting of inulin and tetraethoxysilane (TEOS) for use as an adsorbent was successfully synthesized via the sol–gel method in acidic conditions. The hydrolysis and condensation processes were attained in water/ethanol solution. Three molar ratios of inulin:TEOS (1:1, 1:2, and 2:1) were prepared and dried at various temperatures (50, 60, and 70 °C). The optimized molar ratio of 2:1 with a drying temperature of 70 °C was found to obtain the best morphology and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It has been reported that powdered roots of chicory and dahlia contain large amounts of inulin which have the ability to adsorb toxic metal ions and organic compounds by reacting with –CO and –OH groups of inulin . Inulin is nontoxic, safe, economical, and most commonly available biopolymer which make it suitable to prepare composite materials for adsorption of organic compounds . The extent of polymerization, as well as the number of branches, plays a role in the functioning of Inulin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that powdered roots of chicory and dahlia contain large amounts of inulin which have the ability to adsorb toxic metal ions and organic compounds by reacting with –CO and –OH groups of inulin . Inulin is nontoxic, safe, economical, and most commonly available biopolymer which make it suitable to prepare composite materials for adsorption of organic compounds . The extent of polymerization, as well as the number of branches, plays a role in the functioning of Inulin.…”
Section: Introductionmentioning
confidence: 99%
“…41 Inulin is nontoxic, safe, economical, and most commonly available biopolymer which make it suitable to prepare composite materials for adsorption of organic compounds. 42 The extent of polymerization, as well as the number of branches, plays a role in the functioning of Inulin. Recently, the potential of ZnO/graphene oxide/inulin was demonstrated for the adsorptive extraction of fluoroquinolone antibiotic enrofloxacin from aqueous environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The form of functionalization carried out was coating on the surface of ZnO particles with tetraethyl orthosilicate (TEOS) compounds. TEOS is used as a source of silanol groups that act as a capping agent in adsorbent synthesis because it will have an impact on ZnO particles so that they have a large surface area and high metal absorption [7]. Synthesis of ZnO particles uses various methods, namely the sol-gel method [8], hydrothermal [9], solvothermal [10], spray pyrolysis [11], microwave-assisted [12], and coprecipitation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the conventional uses of carrageenan alone, hybrid systems of carrageenan with various natural substrates have been reported to be good candidates for the adsorption of pharmaceutical contaminants from water [39,[44][45][46]. Sol-gel-derived hybrid materials, where interpenetrating organic polymers and inorganic components are covalently bonded, have shown promise as sorbents [47][48][49]. Silicon alkoxide coupling agents have been essential in preparing such hybrid materials to enhance the compatibility between the inorganic and organic components.…”
Section: Introductionmentioning
confidence: 99%